Fan fiction genres : gender, sexuality, relationships and family in the fandoms "Star Trek" and "Supernatural" - Goldmann, Julia Elena (Critical studies in media and communication., 2022)
What if James T. Kirk and Spock had a baby, left the Enterprise and moved to New Vulcan to live happily ever after?Fan fiction plots like this are a strong testament of fans' endless creativity. Not only do the authors invent their own storylines but they have developed a generic definition of content across fandoms according to the relationship present in the text. Classification is therefore profoundly related to gender and sexuality. Julia Elena Goldmann examines these generic structures and formulaic patterns comparatively in Star Trek and Supernatural fan fiction. She also focuses on the interplay of the concepts of gender, sexuality, relationships and depictions of family in these texts.